The legislative road to Silicon Valley - Armour, J (Oxford University Press, 2006)
Must policymakers seeking to replicate the success of Silicon Valley's venture capital market first copy other US institutions, such as deep and liquid stock markets? Or can legislative reforms alone make a significant difference? In this paper, we compare the economic and legal determinants of venture capital investment, fundraising, and exits. We introduce a cross-sectional and time series empirical analysis across 15 countries and 14 years of data spanning an entire business cycle. We show that liberal bankruptcy laws stimulate entrepreneurial demand for venture capital; that government programmes more often hinder than help the development of private equity, and that the legal environment matters as much as the strength of stock markets. Our results imply generalizable lessons for legal reform.